2020
DOI: 10.1111/jcmm.15513
|View full text |Cite
|
Sign up to set email alerts
|

Circ‐AKT3 inhibits the accumulation of extracellular matrix of mesangial cells in diabetic nephropathy via modulating miR‐296‐3p/E‐cadherin signals

Abstract: Diabetic nephropathy is a leading cause of end‐stage renal disease globally. The vital role of circular RNAs (circRNAs) has been reported in diabetic nephropathy progression, but the molecular mechanism linking diabetic nephropathy to circRNAs remains elusive. In this study, we investigated the significant function of circ‐AKT3/miR‐296‐3p/E‐cadherin regulatory network on the extracellular matrix accumulation in mesangial cells in diabetic nephropathy. The expression of circ‐AKT3 and fibrosis‐associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Circ_00037128/miR-17-3p/AKT3 axis also facilitated DKD progression via modulating MCs proliferation and fibrosis ( 93 ). On the contrary, another two circRNAs, circ-AKT3 and circ_LARP4, were found to be down-regulated in HG-stimulated MCs model ( 94 , 95 ). Circ-AKT3 inhibited ECM accumulation via modulating miR-296-3p/E-cadherin signals, while circ_LARP4 overexpression could repress MCs proliferation and fibrosis but increase cell apoptosis by sponging miR-424.…”
Section: Circrnas As Therapeutic Targets For Kidney Diseasesmentioning
confidence: 88%
“…Circ_00037128/miR-17-3p/AKT3 axis also facilitated DKD progression via modulating MCs proliferation and fibrosis ( 93 ). On the contrary, another two circRNAs, circ-AKT3 and circ_LARP4, were found to be down-regulated in HG-stimulated MCs model ( 94 , 95 ). Circ-AKT3 inhibited ECM accumulation via modulating miR-296-3p/E-cadherin signals, while circ_LARP4 overexpression could repress MCs proliferation and fibrosis but increase cell apoptosis by sponging miR-424.…”
Section: Circrnas As Therapeutic Targets For Kidney Diseasesmentioning
confidence: 88%
“…Gpnmb Naglu NF-κB activation Inflammation circ_0114427 (Cao et al, 2020) miR-494 AFT3 NF-κB activation circ-AKT3 (Xu et al, 2020) miR-144-5p Wnt/β-catenin pathway Wnt/β-catenin activation circ-YAP1 (Huang et al, 2020) miR-21-5p PI3K/AKT/mTOR pathway PI3K/AKT/mTOR activation circ-VMA21 (Shi et al, 2020) miR-9-3p SMG1 Oxidative stress Chronic kidney disease circHLA-C (Luan et al, 2018) miR-150 Undefined Fibrosis-associated genes express circRNA_15698 (Hu et al, 2019) miR-185 TGF-β1 Extracellular matrix-related protein synthesis circ_WBSCR17 (Li et al, 2020a) miR-185-5p SOX6 ECM accumulation circRNA_002453 (Ouyang et al, 2018) Undefined Undefined Biomarker in blood circ_DLGAP4 (Bai et al, 2020) miR-145 ERBB3/NF-κB/MMP-2 pathway Inflammation circLRP6 miR-205 HMGB 1/TLR4/NF-κB pathway Inflammation circRNA_010383 (Peng et al, 2020) miR-135a TRPC1 ECM accumulation circ-AKT3 (Tang et al, 2020) miR-296-3p E-cadherin ECM accumulation circNr1h4 (Lu et al, 2020) miR-155-5p Far1 Reactive oxygen cANRIL (Deng et al, 2019) miR-9 NF-κB and JNK/p38 pathways Inflammation Renal cell carcinom has_circ_001895 miR-296-5p SOX12 Promoting proliferation, migration, invasion, inhibiting apotosis circEGLN3 (Lin and Cai, 2020) miR-1299 IRF7 Promoting proliferation, migration, invasion, inhibiting apotosis circNRIP1 (Dong et al, 2020) miR-505 AMPK and PI3KL/AKT/mTOR pathways Promoting proliferation, migration, invasion, inhibiting apotosis circNUP98 (Yu et al, 2020) miR-567 PRDX3 Promoting proliferation, migration, invasion, inhibiting apotosis has_circ_0072309 miR-100 PI3KL/AKT/mTOR Inhibiting proliferation, migration, invasion, promoting apotosis circC3P1 miR-21/PTEN PI3K/AKT and NF-κB Inhibiting proliferation, migration, invasion, promoting apotosis circFNDC3B miR-99a JAK1/STAT3 and MEK/ERK pathways Promoting proliferation, migration circ-ZNF652 (Zhang and Guo, 2020) miR-205 JAK1/STAT3 and MEK/ERK pathways Promoting proliferation, migration circ-ZNF609 (Xiong et al, 2019) miR-138-5p FOXP4 Promoting proliferation, invasion circDHX33 (Wang et al, 2020) miR-498-3p MERK Promoting proliferation, invasion circHIPK3 miR-508-3p CXCL13 Promoting proliferation, migration, invasion circUBAP2 (Sun et al, 2020) miR-148a-3p FOXK2 Promoting proliferation, migration, invasion circ_001842 (Zeng et al, 2020) miR-502-5p SLC39A14 Promoting proliferation, migration, invasion cRAPGEF5 miR-27a-3p TXNIP Inhibiting proliferation, migration has_circ_0001451 associated genes (Zhou et al, 2013;…”
Section: Circular Rnas In Chronic Kidney Diseasesmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is characterized by the proliferation of mesangial cells and the accumulation of the extracellular matrix (Wang et al, 2018; Lu et al, 2019 ), and there is also increasing evidence of the role of the inflammatory response in developing DN ( Yaribeygi et al, 2019 ). circ-AKT3 inhibited the extracellular matrix accumulation through modulating miR-296-3p/E-cadherin signals in diabetic nephropathy mesangial cells ( Tang et al, 2020 ). circRNA_15698 is upregulated in db/db mice, and acts as an miR-185 sponge to regulate TGF-β1 expression, which promoting extracellular matrix-related protein synthesis ( Hu et al, 2019 ).…”
Section: Circular Rnas In Chronic Kidney Diseasesmentioning
confidence: 99%
“…Diabetic renal fibrosis is caused by the unbalanced metabolism of ECM molecules that may eventually lead to renal failure. Previous studies reported that circ-AKT3 inhibits ECM accumulation in mesangial cells of DN by regulating miR-296-3p/E-cadherin signals [ 13 ]. miRNA imbalance is closely related to the occurrence of diabetic renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%